2013
DOI: 10.1186/2193-1801-2-174
|View full text |Cite
|
Sign up to set email alerts
|

Influence of socio-demographic factors on awareness of HIV/AIDS among Bangladeshi garment workers

Abstract: The study was conducted to assess the level of awareness on HIV/AIDS (Acquired Immune Deficiency Syndrome) and the Influence of different socio-demographic factors among the garment workers in Bangladesh. This cross sectional study was carried out among 303 workers in three selected garment factories in Dhaka city from July 2010 to June 1011. Data were collected by face to face interview through a predesigned questionnaire containing desired information. The majority of workers (76.6%) were within the 17–19 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 4 publications
(5 reference statements)
3
23
0
Order By: Relevance
“…Studies showed that there was an association between age and level of intelligence of garment women workers. Those who were in the age group of 17-19 years had better understanding on HIV than below the age of fourteen (Hasan et al, 2013). Comparing to illiterate apparel workers and literate wear labourers were 3.37 times more educated to have knowledge on HIV.…”
Section: Difference Of Hiv/aids Knowledge At Several Categoriesmentioning
confidence: 99%
See 4 more Smart Citations
“…Studies showed that there was an association between age and level of intelligence of garment women workers. Those who were in the age group of 17-19 years had better understanding on HIV than below the age of fourteen (Hasan et al, 2013). Comparing to illiterate apparel workers and literate wear labourers were 3.37 times more educated to have knowledge on HIV.…”
Section: Difference Of Hiv/aids Knowledge At Several Categoriesmentioning
confidence: 99%
“…Almost all of the workers (98.3%) heard this word in get-up factories of Bangladesh. Around ninety one per cent of them knew that this attack is transmissible from one person to another (Hasan et al, 2013). Additionally, it breaks the immune system and makes a man too vulnerable to any kind of unsoundness-cultured by more than seventy per cent of blue-collar employees (Mondal et al, 2008).But the apprehensive on this facet is not sufficient amidst them.…”
Section: Knowledge/awareness On Hiv Among Garment Women Workers In Bamentioning
confidence: 99%
See 3 more Smart Citations